Enrichment of GABAA Receptor α-Subunits on the Axonal Initial Segment Shows Regional Differences - Gao, Yudong; Heldt, Scott A. (Frontiers in Cellular Neuroscience, 2016)
Although it is generally recognized that certain α-subunits of γ-aminobutyric acid type A receptors (GABAARs) form enriched clusters on the axonal initial segment (AIS), the degree to which these clusters vary in different brain areas is not well known. In the current study, we quantified the density, size, and enrichment ratio of fluorescently labeled α1-, α2-, or α3-subunits aggregates co-localized with the AIS-marker ankyrin G (AnkG) and compared them to aggregates in non-AIS locations among different brain areas including hippocampal subfields, basal lateral amygdala (BLA), prefrontal cortex (PFC) and sensory cortex (CTX). We found regional differences in the enrichment of GABAAR α-subunits on the AIS. Significant enrichment was identified in the CA3 of hippocampus for α1-subunits, in the CA1, CA3, and BLA for α2-subunits, and in the BLA for α3-subunits. Using α-subunit knock-out (KO) mice, we found that BLA enrichment of α2- and α3-subunits were physiologically independent of each other, as the enrichment of one subunit was unaffected by the genomic deletion of the other. To further investigate the unique pattern of α-subunit enrichment in the BLA, we examined the association of α2- and α3-subunits with the presynaptic vesicular GABA transporter (vGAT) and the anchoring protein gephyrin (Geph). As expected, both α2- and α3-subunits on the AIS within the BLA received prominent GABAergic innervation from vGAT-positive terminals. Further, we found that the association of α2- and α3-subunits with Geph was weaker in AIS versus non-AIS locations, suggesting that Geph might be playing a lesser role in the enrichment of α2- and α3-subunits on the AIS. Overall, these observations suggest that GABAARs on the AIS differ in subunit composition across brain regions. As with somatodendritic GABAARs, the distinctive expression pattern of AIS-located GABAAR α-subunits in the BLA, and other brain areas, likely contribute to unique forms of GABAergic inhibitory transmission and pharmacological profiles seen in different brain areas.